Method for preparing lithium ion battery
Through the combination of two-step liquid injection technology and specific additives, the problem of low temperature and long cycle performance of lithium-ion batteries under low liquid injection volume conditions is solved, and high energy efficiency and long cycle stability battery performance is achieved.
Patent Information
- Application Number
- CN202411586128.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Under low injection volume conditions, the low temperature and long cycle performance of lithium-ion batteries are challenged, especially in the later stages of the cycle, which may cause electrolyte drying, resulting in performance decay and diving.
Using two-step liquid injection technology, three additives: vinyl carbonate, 1,3-propanesulfonolide and fluorovinyl carbonate are used to optimize the generation and repair of the SEI film through the combination of the first electrolyte and the second electrolyte, and improve the initial performance and long-term cycle stability of the battery.
It significantly improves the overall stability and battery performance of the SEI film, ensures the high energy-efficiency performance of the battery under low temperature conditions, and maintains excellent cycling stability during long-term use, achieving an effective balance between low interface impedance and long cycle stability.
Smart Images

Figure CN119108659B_ABST
Abstract
Description
Technical Field
[0001] The embodiments of the present application relate to the field of battery technology, and in particular to a method for preparing a lithium-ion battery. Background Art
[0002] Lithium-ion batteries have been widely used in electric vehicles, energy storage, power tools, aerospace and other fields due to their high energy density, high voltage, long cycle and environmental friendliness. As an important component of the lithium-ion battery system, the electrolyte is a bridge connecting the positive and negative electrodes, has the function of transmitting lithium ions, and determines the efficiency of battery energy transmission.
[0003] In order to meet the development needs of large capacity and high energy density, the surface density and compaction density of the pole piece are continuously improved during the battery design process, while reducing the amount of electrolyte injection. Under such low injection conditions, the low temperature and long cycle performance of the battery are further challenged, especially in the late cycle, the electrolyte may dry up, causing a series of performance degradation and diving problems.
[0004] Therefore, there is an urgent need for a lithium-ion battery preparation method that provides high energy efficiency and long cycle life under low injection volume conditions to meet the complex needs of the energy storage field. Summary of the invention
[0005] The embodiment of the present application provides a method for preparing a lithium-ion battery, which is at least beneficial for maintaining the lithium-ion battery with high energy efficiency and long cycle life under the condition of low injection volume.
[0006] According to some embodiments of the present application, on the one hand, an embodiment of the present application provides a method for preparing a lithium-ion battery, comprising: providing a positive electrode sheet, a negative electrode sheet and a separator; winding or stacking the positive electrode sheet, the negative electrode sheet and the separator and placing them in a shell to form an initial battery cell, wherein the separator is located between the positive electrode sheet and the negative electrode sheet; performing a first liquid injection process on the initial battery cell, wherein a first electrolyte is injected into the initial battery cell in the step of the first liquid injection process, wherein the components of the first electrolyte include: 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt and a non-aqueous organic solvent; performing a formation process on the initial battery cell; A second liquid injection process is performed on the initial battery cell, in which a second electrolyte is injected into the initial battery cell, and components of the second electrolyte include: 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of a wetting stabilizer and a non-aqueous organic solvent; wherein, the first electrolyte or the second electrolyte also includes: at least one of 1,3-propane sultone or fluoroethylene carbonate, and the content of 1,3-propane sultone is 0.1wt%~2wt%, and the content of fluoroethylene carbonate is 0.1wt%~2wt%.
[0007] In some embodiments, the first electrolyte includes 0.1 wt % to 2 wt % of 1,3-propane sultone and 0.1 wt % to 2 wt % of fluoroethylene carbonate.
[0008] In some embodiments, after performing a formation process on the initial battery cell and before performing a second liquid injection process on the initial battery cell, the process further includes: performing a liquid replenishment process on the initial battery cell, in which the first electrolyte is replenished into the initial battery cell.
[0009] In some embodiments, before the initial battery cell is subjected to a formation process, the method includes: weighing the initial battery cell to obtain a first mass of the initial battery cell; after the initial battery cell is subjected to the formation process, the method includes: weighing the initial battery cell to obtain a second mass of the initial battery cell; the mass of the first electrolyte replenished in the replenishment process is the difference between the first mass and the second mass.
[0010] In some embodiments, the wetting stabilizer is selected from: 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether, N-ethylperfluorooctanesulfonamidoethyl methacrylate, fluorobenzene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, hexafluoropropyl glycol and hexafluoropropylene oxide.
[0011] In some embodiments, the first electrolyte includes: at least one of a positive electrode film-forming agent or a negative electrode film-forming agent, the content of the positive electrode film-forming agent is 0.5wt%~3wt%, and the content of the negative electrode film-forming agent is 0.5wt%~2wt%.
[0012] In some embodiments, the first electrolyte accounts for 65 wt % to 90 wt % of the total mass of the first electrolyte and the second electrolyte.
[0013] In some embodiments, the injection amount of the first electrolyte is 3.5 g / Ah to 4 g / Ah; the injection amount of the second electrolyte is 3.5 g / Ah to 4 g / Ah.
[0014] In some embodiments, the formation process includes: a first high-temperature static step, a negative pressure formation step, and an aging static step.
[0015] In some embodiments, after performing the second liquid injection process on the initial battery cell, the method further includes: performing a second high-temperature static process on the initial battery cell, wherein the temperature of the second high-temperature static process is greater than the temperature of the first high-temperature static process.
[0016] The technical solution provided by the embodiments of the present application has at least the following advantages:
[0017] The preparation method of the lithium-ion battery provided in the embodiment of the present application can significantly improve the overall stability of the SEI film and the battery performance by using the two-step liquid injection technology and comprehensively utilizing the advantages of three additives: vinyl carbonate, 1,3-propane sultone and fluoroethylene carbonate. Fluorinated vinyl carbonate is beneficial to ensuring the low temperature and high energy efficiency performance of the battery; 1,3-propane sultone is beneficial to enhancing the density and stability of the SEI film, especially providing additional protection under high temperature conditions; vinyl carbonate helps maintain and repair the SEI structure during high temperature cycles. By synergistically optimizing the function and application timing of each additive, not only the initial performance of the battery is improved, but also excellent cycle stability is maintained during long-term use. The two-step liquid injection technology successfully achieves an effective balance between the low interfacial impedance and long cycle stability of the battery with a low total electrolyte dosage. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] One or more embodiments are exemplarily illustrated by the pictures in the corresponding drawings. These exemplified descriptions do not constitute a limitation on the embodiments. Unless otherwise specified, the pictures in the drawings do not constitute a scale limitation. In order to more clearly illustrate the embodiments of the present application or the technical solutions in the traditional technology, the drawings required for use in the embodiments are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A flowchart corresponding to the method for preparing a lithium-ion battery provided in an embodiment of the present application;
[0020] Figure 2 A schematic diagram of the electrochemical structure of a lithium-ion battery is provided for the embodiment of the present application;
[0021] Figure 3 Formulas of the first electrolyte and the second electrolyte corresponding to Comparative Example 1 and Examples 2 to 17 provided in the embodiments of the present application;
[0022] Figure 4 The test results corresponding to Comparative Example 1 and Examples 2 to 17 provided in the embodiments of the present application. DETAILED DESCRIPTION
[0023] As can be seen from the background technology, there is an urgent need for a lithium-ion battery preparation method that provides high energy efficiency and long cycle life under low injection volume conditions to meet the complex needs in the energy storage field.
[0024] Taking lithium iron phosphate batteries as an example, at present, additives are usually used in the electrolyte of lithium iron phosphate batteries to improve the high temperature performance and life of lithium iron phosphate, but these additives often lead to limited energy efficiency of lithium iron phosphate batteries at room temperature and low temperature. Although the energy efficiency at room temperature and low temperature can be improved by adjusting the electrolyte formula, this usually sacrifices the performance of lithium iron phosphate batteries in high temperature environments. For example, the related art adopts a secondary injection method to balance high temperature performance and kinetic performance for different additives. However, these methods do not fully consider the special requirements of the energy storage field for battery performance, especially the problems of electrolyte drying up and battery performance attenuation under low injection volume conditions. Another related technology adopts a secondary injection method to improve the high temperature storage performance of the battery by adjusting the content of high temperature additives at different stages, but there is still room for improvement in the performance of energy efficiency at room temperature and low temperature.
[0025] Therefore, it is necessary not only to achieve good cycle performance of the battery under high temperature environment, but also to achieve high energy efficiency and long cycle life of the battery under low injection volume conditions. This requires that in the design of the electrolyte, the performance of the electrolyte at different temperatures must be considered, and the special needs of the battery under low injection volume conditions must also be taken into account. In particular, under normal and low temperature conditions, the electrolyte needs to show higher energy efficiency and stability to cope with potential problems caused by low injection volume, such as uneven reactions inside the battery and accelerated degradation processes.
[0026] Vinyl carbonate (VC) is an important additive in the electrolyte of lithium iron phosphate batteries. VC can form a dense and uniform SEI (solid electrolyte interphase) film on the surface of the negative electrode, improving the high-temperature cycle performance of lithium iron phosphate batteries. As the long-cycle stability of energy storage lithium iron phosphate batteries becomes a core indicator, the amount of VC in the electrolyte formula is also increasing. Although VC is important and effective in the lithium iron phosphate system, the SEI film generated by VC has a large impedance, which will lead to a decrease in battery energy efficiency and low-temperature performance, which is contrary to the low temperature and high energy efficiency requirements of energy storage applications. The contradiction between the need to increase the VC content in the electrolyte for long cycles and the low temperature and high energy efficiency performance of the battery is becoming increasingly prominent.
[0027] In order to balance the above contradictions, a secondary injection method is usually used to optimize the formation of the SEI film. In the first step, a small amount of VC is injected to generate a low-impedance uniform film, and in the second step, more VC is injected to accurately and directionally repair the SEI in the later stage of the cycle. This can take into account the high and low temperature performance requirements of the battery to a certain extent, but the VC content injected in the second step is too high, which is prone to insufficient dispersion and penetration, resulting in the SEI film generated later being too thick locally, which in turn produces microscopic short circuits and weakens the battery's cycle stability. In addition, the reduction in the amount of electrolyte under high energy density design also makes this problem more prominent.
[0028] The preparation method of the lithium-ion battery provided in the embodiment of the present application, through a two-step liquid injection technology, comprehensively utilizes the advantages of three additives: vinyl carbonate, 1,3-propane sultone and fluoroethylene carbonate, which can significantly improve the overall stability of the SEI film and the battery performance. Fluorinated vinyl carbonate is beneficial to ensure the low temperature and high energy efficiency performance of the battery; 1,3-propane sultone is beneficial to enhance the density and stability of the SEI film, especially providing additional protection under high temperature conditions; vinyl carbonate helps maintain and repair the SEI structure during high temperature cycles. By synergistically optimizing the function and application timing of each additive, not only the initial performance of the battery is improved, but also excellent cycle stability is maintained during long-term use. The two-step liquid injection technology successfully achieves an effective balance between the low interfacial impedance and long cycle stability of the battery with a low total electrolyte dosage.
[0029] In the description of the embodiments of the present application, technical terms such as "first" and "second" are only used to distinguish different objects and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features.
[0030] In the description of the embodiments of the present application, “plurality” means more than two, unless otherwise clearly and specifically defined.
[0031] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.
[0032] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists, A and B exist at the same time, and B exists. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0033] In the description of the embodiments of the present application, when a certain component “includes” another component, unless otherwise stated, other components are not excluded and other components may be further included.
[0034] The terms used in the description of the various described embodiments herein are used only to describe specific embodiments and are not intended to be limiting. As used in the description of the various described embodiments and the appended claims, "components" are also intended to include plural forms unless the context clearly indicates otherwise.
[0035] The following will describe the various embodiments of the present application in detail with reference to the accompanying drawings. However, it will be appreciated by those skilled in the art that in the various embodiments of the present application, many technical details are provided in order to enable the reader to better understand the present application. However, even without these technical details and various changes and modifications based on the following embodiments, the technical solution claimed in the present application can be implemented.
[0036] Figure 1 This is a flow chart corresponding to the method for preparing a lithium-ion battery provided in an embodiment of the present application.
[0037] refer to Figure 1 , a method for preparing a lithium ion battery, comprising:
[0038] Step 101: Provide a positive electrode sheet, a negative electrode sheet and a separator.
[0039] The positive electrode sheet may include a positive electrode current collector and a positive electrode material layer covering the surface of the positive electrode current collector, wherein the positive electrode material layer includes a positive electrode material and a positive electrode adhesive material, and the positive electrode material is dispersed in the positive electrode adhesive material.
[0040] The negative electrode sheet may include a negative electrode current collector and a negative electrode material layer covering the surface of the negative electrode current collector, wherein the negative electrode material layer includes a negative electrode material and a negative electrode adhesive material, and the negative electrode material is dispersed in the negative electrode adhesive material.
[0041] In a specific example, the material of the positive electrode current collector is aluminum foil, and the material of the negative electrode current collector is copper foil.
[0042] The positive electrode material can be selected from lithium iron phosphate, lithium cobalt oxide, lithium manganese oxide or ternary materials.
[0043] The negative electrode material can be selected from natural graphite, artificial graphite, soft carbon or hard carbon.
[0044] The positive electrode adhesive material and the negative electrode adhesive material can both be selected from sodium hydroxycellulose, polyvinylidene fluoride or styrene-butadiene rubber.
[0045] The diaphragm can be selected from polypropylene (PP) microporous diaphragm, polyethylene (PE) microporous diaphragm, PE / PP composite microporous diaphragm, propylene and ethylene copolymer diaphragm or polyethylene homopolymer diaphragm, etc.
[0046] Step 102: The positive electrode sheet, the negative electrode sheet and the separator are wound or stacked and placed into a casing to form an initial battery cell, with the separator being located between the positive electrode sheet and the negative electrode sheet.
[0047] The winding process is the process of stacking the positive electrode sheet, separator and negative electrode sheet in sequence and winding them into a core roll in a certain order. It is mainly used to produce square and cylindrical lithium batteries.
[0048] Lamination is a method of assembling a battery cell by stacking positive electrode sheets, separators, negative electrode sheets and other components layer by layer. The lamination process can generally be divided into lamination and folding. Compared with winding, the lamination winding process requires higher tension control. Lamination is mainly used in the production of large square batteries, ultra-thin batteries and special-shaped batteries.
[0049] Step 103: Perform the first liquid injection process on the initial battery cell. In the first liquid injection process, the first electrolyte is injected into the initial battery cell. The components of the first electrolyte include: 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt and non-aqueous organic solvent. The first electrolyte mainly composed of a low-concentration additive combination is conducive to the formation of a low-polarization, uniform and dense SEI film in the subsequent formation process, and effectively discharges side reaction gases, which avoids the problem that a large amount of additives are difficult to fully react in a single use. In addition, by controlling the combination and ratio of additives, it is conducive to the generation of a better interface layer, i.e., SEI film.
[0050] In the first electrolyte, the mass fraction of each component is expressed as the mass ratio of the component to the total mass of the first electrolyte.
[0051] For example, the mass fraction of vinylene carbonate in the first electrolyte is 0.5wt%~2wt%, which is expressed as the proportion of the mass of vinylene carbonate to the total mass of the first electrolyte is 0.5wt%~2wt%, for example, 0.5wt%~0.8wt%, 0.8wt%~1.2wt%, 1.2wt%~1.6wt% or 1.6wt%~2wt%, and specifically can be 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%.
[0052] For example, the mass fraction of the lithium salt in the first electrolyte is 5wt%~15wt%, which is expressed as the proportion of the mass of the lithium salt to the total mass of the first electrolyte is 5wt%~15wt%, for example, 5wt%~9.5wt%, 9.5wt%~12wt% or 12wt%~15wt%, and can specifically be 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt% or 15wt%.
[0053] Among them, the type of lithium salt can be selected from lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6) and lithium hexafluorophosphate (LiPF6).
[0054] In some embodiments, the first electrolyte may further include: at least one of a positive electrode film-forming agent or a negative electrode film-forming agent.
[0055] The content of the positive electrode film-forming agent can be 0.1wt%~0.3wt%, 0.3wt%~0.5wt%, 0.5wt%~2wt%, 2wt%~3wt%, 3wt%~4wt% or 4wt%~5wt%, specifically 0.1wt%, 0.3wt%, 0.5wt%, 2wt%, 2.5wt%, 3.3wt% or 4wt%.
[0056] The positive electrode film-forming agent can be selected from at least one of lithium difluorophosphate, methylene disulfonate, vinyl sulfate, 1,3-propylene sultone, tris(trimethylsilyl)borate, tris(trimethylsilyl)phosphate, 2-propynyl-1-yl 1H-imidazole-1-carboxylate, triallyl isocyanurate, 2,4-toluene diisocyanate, 2-phenyl-1-yl 1H-imidazole-1-sulfonate, hexamethylene diisocyanate, lithium difluorooxalate phosphate, 2-fluoropyridine, lithium bis(oxalatoborate) or lithium difluorooxalateborate.
[0057] The content of the negative electrode film-forming agent may be 0.1wt% to 0.3wt%, 0.3wt% to 0.5wt%, 0.5wt% to 2wt% or 2wt% to 3wt%, specifically 0.1wt%, 0.3wt%, 0.5wt%, 2wt%, 2.5wt% or 3wt%.
[0058] The negative electrode film-forming agent can be selected from at least one of vinyl sulfate, methylene methanedisulfonate, lithium difluorooxalatoborate, propylene sulfate, lithium difluorooxalatophosphate, tris(trimethylsilyl)phosphate, lithium bis(oxalatoborate), methylene 1,3-propylenedisulfonate, trimethylsilylphosphate, and methylene methanedisulfonate.
[0059] In some specific embodiments, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.5wt%~3wt% of positive electrode film-forming agent and non-aqueous organic solvent; or, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.5wt%~2wt% of negative electrode film-forming agent and non-aqueous organic solvent; or, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.5wt%~3wt% of positive electrode film-forming agent, 0.5wt%~2wt% of negative electrode film-forming agent and non-aqueous organic solvent.
[0060] The non-aqueous organic solvent of the first electrolyte can be selected from two or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl acetate, methyl propionate, methyl acetate, ethyl propionate, propyl propionate, ethyl butyrate, methyl propyl carbonate, propylene carbonate, γ-butyrolactone and γ-valerolactone. In addition, cyclic carboxylic acid esters, chain carboxylic acid esters, ether compounds and sulfone compounds can also be added to the first electrolyte to optimize the performance and stability of the first electrolyte.
[0061] In a specific example, the non-aqueous organic solvent of the first electrolyte is composed of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, wherein the mass ratio of ethylene carbonate to the non-aqueous organic solvent is 30%, the mass ratio of ethyl methyl carbonate to the non-aqueous organic solvent is 30%, and the mass ratio of dimethyl carbonate to the non-aqueous organic solvent is 40%.
[0062] Step 104: Perform a formation process on the initial battery cell.
[0063] The formation process generally includes: a first high-temperature standing step, a negative pressure formation step, and an aging standing step.
[0064] The temperature range of the first high-temperature standing step can be 45°C to 60°C, such as 45°C to 50°C, 50°C to 55°C or 55°C to 60°C, and can be specifically 45°C, 48°C, 50°C, 53°C, 56°C or 60°C; the time range can be 36h to 72h, such as 36h to 45h, 45h to 62h or 62h to 72h, and can be specifically 36h, 38h, 40h, 45h, 50h, 57h, 60h, 66h, 70h or 72h. Above 40°C is high-temperature formation, which can accelerate the speed of electrochemical reaction and the growth speed of SEI film and reduce the time required for formation.
[0065] The negative pressure formation step may include a first formation step and a second formation step. In the first formation step, the initial battery cell is charged to a charge state (SOC) of 5% to 10% with a rate current of 0.01C to 0.1C and then discharged; in the second formation process step, the initial battery cell is charged to a charge state of 10% to 85% with a rate current of 0.1C to 0.5C and then discharged. In this way, a small current is first used to form the SEI film molecules to make them dense and stable. The activation time of the small rate current is long but the polarization is small. The generated SEI film is mostly generated by a single molecule reaction, with a dense structure and few irreversible reactions. The subsequent high current formation can accelerate the formation speed of the SEI film and reduce the formation time, but it is more likely to cause a two-electron reaction, generate more inorganic components, and have a loose structure but is conducive to the infiltration of the electrolyte. The use of a step-by-step formation method can improve the battery's charge and discharge efficiency and reduce internal resistance. By balancing the formation quality of the SEI film and the wetting effect of the electrolyte, the battery can have better cycle performance.
[0066] Among them, the rate current in the first formation step can be 0.01C~0.05C, 0.05C~0.08C or 0.08C~0.1C, specifically 0.01C, 0.05C, 0.8C or 0.1C; the SOC in the first formation step can be 5%~7%, 7%~9% or 9%~10%, specifically 5%, 6%, 7%, 8%, 9% or 10%. The rate current in the second formation step can be 0.1C~0.3C, 0.3C~0.4C or 0.4C~0.5C, specifically 0.1C, 0.25C, 0.38C, 0.46C or 0.5C; the SOC in the second formation step can be 10%~25%, 25%~45%, 45%~60%, 60%~80% or 80%~85%, specifically 10%, 15%, 26%, 34%, 45%, 60%, 73%, 80% or 85%.
[0067] In some embodiments, the time of the first formation step is controlled at 0.5h~10h, for example, 0.5h~2h, 2h~6h, 6h~8h or 8h~10h, and can be specifically 0.5h, 0.8h, 1h, 3h, 5h, 8h or 10h; the time of the second formation step is controlled at 1.6h~8h, for example, 1.6h~3h, 3h~5h, 5h~7h or 7h~5h, and can be specifically 1.6h, 2h, 4h, 5h, 6h or 8h.
[0068] In a specific embodiment, the upper limit voltage of the first formation step and the second formation step are both set to 3.65V.
[0069] The vacuum degree of the vacuum pumping in the negative pressure formation step can be -10KPa~-100KPa, -10Kpa~-20Kpa, -20Kpa~-50Kpa or -50Kpa~-100Kpa, specifically -10KPa, -20KPa, -50KPa, -75KPa or -100KPa, etc.
[0070] The temperature of the static aging step can be 45°C~60°C, for example 45°C~50°C, 50°C~55°C or 55°C~60°C, specifically 45°C, 48°C, 50°C, 53°C, 56°C or 60°C; the time range can be 18h~24h, for example 18h~20h, 20h~22h or 22h~24h, specifically 18h, 19h, 20h, 21h, 22h, 23h or 24h.
[0071] Step 105: Perform a second liquid injection process on the initial battery cell. In the second liquid injection process, a second electrolyte is injected into the initial battery cell. The components of the second electrolyte include: 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of wetting stabilizer and non-aqueous organic solvent. The second electrolyte contains a wetting stabilizer and a high concentration of vinylene carbonate, wherein the wetting stabilizer can enhance the coverage of the electrode, reduce surface tension, improve the solubility of the second electrolyte, and inhibit the performance degradation caused by the reduction of the electrolyte; the high concentration of vinylene carbonate can effectively repair the formed SEI film, thereby facilitating the improvement of the high temperature performance and cycle life of the battery cell.
[0072] In the second electrolyte, the mass fraction of each component is expressed as the mass ratio of the component to the total mass of the second electrolyte.
[0073] For example, the mass fraction of vinylene carbonate in the second electrolyte is 5wt%~20wt%, which is expressed as the proportion of the mass of vinylene carbonate to the total mass of the second electrolyte is 5wt%~20wt%, and can be specifically 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt% or 20wt%.
[0074] For example, the mass fraction of the lithium salt in the second electrolyte is 5wt%~15wt%, which is expressed as the proportion of the mass of the lithium salt to the total mass of the second electrolyte is 5wt%~15wt%, and can be specifically 5wt%, 5.5wt%, 6wt%, 6.5wt%, 7wt%, 7.5wt%, 8wt%, 8.5wt%, 9wt%, 9.5wt%, 10wt%, 10.5wt%, 11wt%, 11.5wt%, 12wt%, 12.5wt%, 13wt%, 13.5wt%, 14wt%, 14.5wt% or 15wt%.
[0075] For example, the mass fraction of the wetting stabilizer in the second electrolyte is 0.005wt%-30wt%, which is expressed as the proportion of the wetting stabilizer to the total mass of the second electrolyte is 0.005wt%-30wt%, and can be specifically 0.005wt%, 0.01wt%, 0.02wt%, 0.03wt%, 0.04wt%, 0.05wt%, 0.06wt%, 0.07wt%, 0.08wt%, 0.09wt%, 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%. t%, 0.8wt%, 0.9wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 1 4wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, 21wt%, 22wt%, 23wt%, 24wt%, 25wt%, 26wt%, 27wt%, 28wt%, 29wt% or 30wt%.
[0076] Among them, the wetting stabilizer can be selected from: 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether, N-ethyl perfluorooctanesulfonamidoethyl methacrylate, fluorobenzene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, hexafluoropropyl glycol and hexafluoropropylene oxide. These wetting stabilizers significantly improve the wettability and stability of the electrolyte through their unique structure and functional properties. For example, fluorobenzene and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether can significantly improve the stability of the electrolyte and the wettability of the electrode surface, thereby improving the overall performance of the battery. In addition, fluorine compounds such as 1,3-dioxane and its derivatives are used in the electrolyte, which not only improves the wettability of the electrolyte, but also forms a stable SEI film on the electrode surface, thereby enhancing the cycle performance and energy efficiency of the battery. By combining these wetting and stabilizing additives, the formulation of the second electrolyte can be flexibly adjusted to meet the needs of different types of lithium-ion batteries, significantly improving the overall performance and service life of the battery.
[0077] The second electrolyte may further include auxiliary additives, and the content of the auxiliary additives in the second electrolyte is less than 2 wt %.
[0078] The auxiliary additives may be selected from: fluoroethylene carbonate, vinylene carbonate, lithium difluorooxalate borate, lithium difluorophosphate, lithium dioxalate borate, methylene disulfonate, vinyl sulfate, triallyl phosphate, 1,3-propane sultone, triplyl phosphate, 1,3-propylene sultone, lithium bis(fluorosulfonyl)imide, fluorobenzene, trifluoroethoxyethylene carbonate, 2-methylmaleic anhydride, difluoroethylene carbonate, succinic anhydride, tris(trimethylsilyl)phosphate, vinyl sulfite, at least one of hexamethylene diisocyanate. These film-forming additives and production-inhibiting additives are beneficial to maintaining the stability of the battery during use.
[0079] The non-aqueous organic solvent of the second electrolyte can be selected from two or more of ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, propyl acetate, methyl propionate, methyl acetate, ethyl propionate, propyl propionate, ethyl butyrate, methyl propyl carbonate, propylene carbonate, γ-butyrolactone and γ-valerolactone. In addition, cyclic carboxylic acid esters, chain carboxylic acid esters, ether compounds and sulfone compounds can also be added to the second electrolyte to optimize the performance and stability of the second electrolyte.
[0080] In a specific example, the non-aqueous organic solvent of the second electrolyte is composed of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, wherein the mass ratio of ethylene carbonate to the non-aqueous organic solvent is 30%, the mass ratio of ethyl methyl carbonate to the non-aqueous organic solvent is 30%, and the mass ratio of dimethyl carbonate to the non-aqueous organic solvent is 40%.
[0081] The first electrolyte or the second electrolyte further includes: at least one of 1,3-propane sultone or fluoroethylene carbonate. The standard decomposition potential of fluoroethylene carbonate is about 1.0V, which is lower than the standard decomposition potential of vinyl carbonate (1.11V). Fluorinated vinyl carbonate has more advantages under low temperature and high power discharge conditions, which is conducive to forming a stable SEI film. The decomposition potential of 1,3-propane sultone is between fluoroethylene carbonate and vinyl carbonate, and 1,3-propane sultone provides moderate interface protection for the components of the SEI film, which helps to improve battery performance and life in high temperature storage and cycling.
[0082] Wherein, the content of 1,3-propane sultone is 0.1wt%~2wt%, and the content of fluoroethylene carbonate is 0.1wt%~2wt%. Specific embodiments are as follows:
[0083] In a first specific example, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.1wt%~2wt% of 1,3-propane sultone and a non-aqueous organic solvent; the second electrolyte may include 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of a wetting stabilizer and a non-aqueous organic solvent.
[0084] In a second specific example, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.1wt%~2wt% of fluoroethylene carbonate and a non-aqueous organic solvent; the second electrolyte may include 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of a wetting stabilizer and a non-aqueous organic solvent.
[0085] In the third specific example, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.1wt%~2wt% of 1,3-propane sultone, 0.1wt%~2wt% of fluoroethylene carbonate and non-aqueous organic solvent; the second electrolyte may include 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of wetting stabilizer and non-aqueous organic solvent. In the first electrolyte, the combined action of fluoroethylene carbonate and 1,3-propane sultone not only pre-treats the electrode interface and generates a stable SEI film, but also helps to eliminate the by-products of the redox reaction of the first electrolyte, reduce the initial polarization, and avoid the problem of a sharp increase in interface impedance caused by the use of a large amount of vinylene carbonate.
[0086] In a fourth specific example, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt and non-aqueous organic solvent; the second electrolyte may include 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of wetting stabilizer, 0.1wt%~2wt% of 1,3-propane sultone and non-aqueous organic solvent.
[0087] In the fifth specific example, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt and non-aqueous organic solvent; the second electrolyte may include 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of wetting stabilizer, 0.1wt%~2wt% of fluoroethylene carbonate and non-aqueous organic solvent.
[0088] In a sixth specific example, the first electrolyte may include 0.5wt%~2wt% of vinylene carbonate, 5wt%~15wt% of lithium salt and non-aqueous organic solvent; the second electrolyte may include 5wt%~20wt% of vinylene carbonate, 5wt%~15wt% of lithium salt, 0.005wt%~30wt% of wetting stabilizer, 0.1wt%~2wt% of 1,3-propane sultone, 0.1wt%~2wt% of fluoroethylene carbonate and non-aqueous organic solvent.
[0089] When 1,3-propane sultone is added to the first electrolyte, the mass fraction of 1,3-propane sultone is 0.1wt%~2wt%, expressed as the mass ratio of 1,3-propane sultone to the total mass of the first electrolyte; when 1,3-propane sultone is added to the second electrolyte, the mass fraction of 1,3-propane sultone is 0.1wt%~2wt%, expressed as the mass ratio of 1,3-propane sultone to the total mass of the second electrolyte. The mass fraction of 1,3-propane sultone in the corresponding first electrolyte or the second electrolyte can specifically be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%.
[0090] When fluoroethylene carbonate is added to the first electrolyte, the mass fraction of fluoroethylene carbonate is 0.1wt%~2wt%, which is expressed as the mass of fluoroethylene carbonate accounts for the total mass of the first electrolyte; when fluoroethylene carbonate is added to the second electrolyte, the mass fraction of fluoroethylene carbonate is 0.1wt%~2wt%, which is expressed as the mass of fluoroethylene carbonate accounts for the total mass ratio of the second electrolyte. The mass fraction of fluoroethylene carbonate in the corresponding first electrolyte or the second electrolyte can specifically be 0.1wt%, 0.2wt%, 0.3wt%, 0.4wt%, 0.5wt%, 0.6wt%, 0.7wt%, 0.8wt%, 0.9wt%, 1.0wt%, 1.1wt%, 1.2wt%, 1.3wt%, 1.4wt%, 1.5wt%, 1.6wt%, 1.7wt%, 1.8wt%, 1.9wt% or 2.0wt%.
[0091] It is understandable that when the amount of additives in the first electrolyte is different, the total mass of the corresponding first electrolyte changes, and the mass of the different additives needs to be adjusted accordingly based on the above ratio. When the amount of additives in the second electrolyte is different, the total mass of the corresponding second electrolyte changes, and the mass of the different additives needs to be adjusted accordingly based on the above ratio.
[0092] Figure 2 A schematic diagram of the electrochemical structure of a lithium-ion battery provided in an embodiment of the present application. To facilitate the explanation of the working principle of a lithium-ion battery, Figure 2 What is shown is the electrochemical principle diagram of the lithium-ion battery, not the structural diagram of the actual lithium-ion battery product.
[0093] The SEI film 212 refers to the interface film formed during the first charging process of the lithium-ion battery due to the redox decomposition of the electrolyte 202 and the deposition on the surface of the negative electrode 211. The SEI film 212 with ion conduction and electronic insulation properties is a guarantee for the long-term stable operation of the lithium-ion battery, and has a vital impact on its capacity, rate, cycle, safety performance, etc.
[0094] The working principle of lithium-ion batteries is as follows: during the charging of lithium-ion batteries, lithium iron phosphate in the positive electrode 221 is deintercalated and converted into iron phosphate. Under the action of the electric field force, the deintercalated lithium ions enter the electrolyte 202 from the surface of the positive electrode 221, pass through the diaphragm 203, and migrate to the surface of the negative electrode 211, and then embed into the lattice of the negative electrode 211 material. During the discharge of lithium-ion batteries, lithium ions in the lattice of the negative electrode 211 material are deintercalated, enter the electrolyte 202, pass through the diaphragm 203, and migrate to the surface of the positive electrode 221, and then re-embed into the lattice of iron phosphate, and the iron phosphate is converted into lithium iron phosphate. Redox reactions continuously occur during the charging and discharging process of lithium-ion batteries, and the compactness and stability of the SEI film are crucial to the performance of lithium-ion batteries.
[0095] The preparation method of the lithium-ion battery provided in the embodiment of the present application can significantly improve the overall stability of the SEI film and the battery performance by using the two-step liquid injection technology and comprehensively utilizing the advantages of three additives: vinyl carbonate, 1,3-propane sultone and fluoroethylene carbonate. Fluorinated vinyl carbonate is beneficial to ensuring the low temperature and high energy efficiency performance of the battery; 1,3-propane sultone is beneficial to enhancing the density and stability of the SEI film, especially providing additional protection under high temperature conditions; vinyl carbonate helps maintain and repair the SEI structure during high temperature cycles. By synergistically optimizing the function and application timing of each additive, not only the initial performance of the battery is improved, but also excellent cycle stability is maintained during long-term use. The two-step liquid injection technology successfully achieves an effective balance between the low interfacial impedance and long cycle stability of the battery with a low total electrolyte dosage.
[0096] In some embodiments, after the initial battery cell is subjected to the second liquid injection process, the process includes: performing a second high-temperature static process on the initial battery cell, wherein the temperature of the second high-temperature static process is greater than the temperature of the first high-temperature static process. The purpose of the first high-temperature static process is to carry out the formation process. In order to form the SEI film under relatively stable conditions and improve the compactness and stability of the SEI film, the temperature of the first high-temperature static process is lower than that of the second high-temperature static process. After the second liquid injection process, in order to improve the efficiency of battery preparation and modify the SEI film using the second electrolyte, the process temperature of the second high-temperature static process can be relatively high.
[0097] The process temperature of the second high-temperature standing is 45°C-60°C, for example, 45°C-50°C, 50°C-56°C or 56°C-60°C, and specifically can be 46°C, 48°C, 50°C, 56°C or 60°C.
[0098] In some embodiments, the first electrolyte accounts for 65wt%~90wt% of the total mass of the first electrolyte and the second electrolyte, for example, it can be 65wt%~73wt%, 73wt%~82wt% or 82wt%~90wt%, etc., specifically 65wt%, 68wt%, 73wt%, 78wt%, 82wt%, 85wt% or 90wt%. In order to ensure the best performance of the battery cell, the first electrolyte should account for 65wt%~90wt% of the total electrolyte. If the injection amount of the first electrolyte in the first injection process is insufficient, the battery cell may not be fully infiltrated, and lithium precipitation problems may easily occur after the formation process; and if the injection amount of the first electrolyte in the first injection process is too large, the additive concentration in the second injection process will be too high, resulting in uneven distribution of additive concentration inside the core. Therefore, the injection amount of the first electrolyte in the first injection process is preferably controlled between 70wt%~90wt% of the total amount, thereby improving the battery and consistency.
[0099] In some embodiments, the injection amount of the first electrolyte is 3.5 g / Ah to 4 g / Ah, for example, 3.5 g / Ah to 3.7 g / Ah, 3.7 g / Ah to 3.8 g / Ah, 3.8 g / Ah to 3.9 g / Ah or 3.9 g / Ah to 4 g / Ah, specifically 3.5 g / Ah, 3.6 g / Ah, 3.7 g / Ah, 3.8 g / Ah, 3.9 g / Ah or 4 g / Ah. / Ah; the injection amount of the second electrolyte is 3.5g / Ah~4g / Ah, for example, 3.5g / Ah~3.7g / Ah, 3.7g / Ah~3.8g / Ah, 3.8g / Ah~3.9g / Ah or 3.9g / Ah~4g / Ah, specifically 3.5g / Ah, 3.6g / Ah, 3.7g / Ah, 3.8g / Ah, 3.9g / Ah or 4g / Ah. Since the electrolyte will continuously undergo redox reactions on the positive and negative electrodes during the operation of the lithium battery, too little injection is not conducive to the cycle life of the lithium-ion battery, and too little injection of the electrolyte will cause some active materials to be unable to penetrate, which is not conducive to the development of the lithium battery capacity, but too much injection of the electrolyte will also cause problems such as reduced energy density and increased cost of the lithium-ion battery. Therefore, the injection amounts of the first electrolyte and the second electrolyte need to be within an appropriate range.
[0100] In some embodiments, after the initial battery cell is subjected to the formation process and before the initial battery cell is subjected to the second liquid injection process, the process further includes: performing a liquid replenishment process on the initial battery cell, and replenishing the first electrolyte into the initial battery cell during the liquid replenishment process. Since the first electrolyte may be lost during the formation process, the liquid replenishment process is performed before the second liquid injection process, and the step of replenishing the first electrolyte is conducive to ensuring that the ratio of the first electrolyte to the second electrolyte is consistent, thereby improving the stability and consistency of the battery.
[0101] The mass of the first electrolyte added during the rehydration process can be the weight loss of the initial battery cell during the formation process. The specific steps include: before the initial battery cell is subjected to the formation process, the initial battery cell is weighed to obtain the first mass of the initial battery cell; after the initial battery cell is subjected to the formation process, the initial battery cell is weighed to obtain the second mass of the initial battery cell; the mass of the first electrolyte added during the rehydration process is the difference between the first mass and the second mass. By measuring the weight loss of the initial battery cell during the formation process, and then supplementing the first electrolyte of the same weight on this basis, it is ensured that the total amount of the first electrolyte in the battery cell is restored to the level after the first injection process. In this way, the loss of the first electrolyte due to volatilization and reaction consumption during the formation process can be compensated, the ratio of the first electrolyte to the second electrolyte can be ensured to be consistent, and the stability of the overall electrolyte formula can be maintained.
[0102] The preparation method of the lithium-ion battery provided in the embodiment of the present application, through a two-step liquid injection technology, comprehensively utilizes the advantages of three additives: vinyl carbonate, 1,3-propane sultone and fluoroethylene carbonate, which can significantly improve the overall stability of the SEI film and the battery performance. Fluorinated vinyl carbonate is beneficial to ensure the low temperature and high energy efficiency performance of the battery; 1,3-propane sultone is beneficial to enhance the density and stability of the SEI film, especially providing additional protection under high temperature conditions; vinyl carbonate helps maintain and repair the SEI structure during high temperature cycles. By synergistically optimizing the function and application timing of each additive, not only the initial performance of the battery is improved, but also excellent cycle stability is maintained during long-term use. The two-step liquid injection technology successfully achieves an effective balance between the low interfacial impedance and long cycle stability of the battery with a low total electrolyte dosage.
[0103] The following are specific embodiments of the present application:
[0104] Figure 3 The formula of the first electrolyte and the second electrolyte corresponding to the comparative example 1 and the examples 2 to 17 provided in the embodiments of the present application. Wherein, I refers to the first liquid injection process, II refers to the second liquid injection process; EC is ethylene carbonate (non-aqueous organic solvent); EMC is ethyl methyl carbonate (non-aqueous organic solvent); DMC is dimethyl carbonate (non-aqueous organic solvent); LiPF6 is lithium hexafluorophosphate (lithium salt); VC is vinylene carbonate (additive); PS is 1,3-propane sultone (additive); FEC is fluoroethylene carbonate (additive); FB is fluorobenzene (wetting stabilizer); TTE is 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether (wetting stabilizer); the unit of the injection amount is g / Ah.
[0105] For ease of explanation, Figure 3In the figure, the solvent is shown as the percentage by mass of the solvent, and the remaining lithium salts and additives are all percentage by mass of the overall formula. Specifically, taking the mass of the first electrolyte as 100g as an example, the mass calculation method of EC in the first electrolyte in Comparative Example 1 is: (100-mass of additive-mass of lithium salt)×30%, wherein the mass of the additive is 3.5%×100g=3.5g, and the mass of the lithium salt is 12.5%×100g=12.5g, then the mass of EC in the first electrolyte is (100-3.5-12.5)×30%=25.2g, and the calculation method of the first electrolyte or the second electrolyte in other embodiments is the same.
[0106] refer to Figure 3 , Comparative Example 1 and Examples 2 to 17 were prepared by the following method, and the specific preparation steps are as follows:
[0107] Step 201: Provide a positive electrode sheet, a negative electrode sheet and a separator.
[0108] The positive electrode sheet includes an aluminum foil and a positive electrode material layer covering the aluminum foil. The positive electrode material layer is composed of lithium iron phosphate, conductive agent SuperP, carbon nanotubes (CNT) and polyvinylidene fluoride (PVDF) in a mass ratio of 95.8:1:0.7:2.5; the negative electrode sheet includes a copper foil and artificial graphite covering the copper foil.
[0109] The surface density of the positive electrode is 452g / m 2 , compacted density is 2.5g / cm 3 ; The surface density of the negative electrode is 215g / m 2 , compacted density is 1.62g / cm 3 .
[0110] Step 202: After the positive electrode sheet, the negative electrode sheet and the separator are wound, they are placed in an aluminum-plastic film shell to form an initial battery cell, and the separator is located between the positive electrode sheet and the negative electrode sheet. After the initial battery cell is baked at high temperature, a moisture test and a helium insulation test are performed on the initial battery cell.
[0111] Step 203: Perform a first liquid injection process on the initial battery cell. In the first liquid injection process, a first electrolyte is injected into the initial battery cell. The components of the first electrolyte correspond to the following: Figure 3 X-1 in which X corresponds to the number of Comparative Example 1 or Examples 2 to 17.
[0112] Step 204: Perform a formation process on the initial battery cell. The formation process includes: a first high-temperature rest step, the temperature of the high-temperature rest process is 45°C, and the time is 36 hours; the first formation step, using a 0.05C rate current to charge the initial battery cell to a SOC of 10% and then discharge, the upper limit voltage is 3.65V; the second formation step, using a 0.25C rate current to charge the initial battery cell to a SOC of 85% and then discharge, the upper limit voltage is 3.65V; an aging rest step, the temperature is 45°C, and the time is 18 hours.
[0113] Step 205: Performing a liquid replenishment process, wherein the mass of the first electrolyte replenished in the liquid replenishment process is the weight loss of the initial battery cell during the formation process.
[0114] Step 206: Perform a second liquid injection process on the initial battery cell, in which a second electrolyte is injected into the initial battery cell. The components of the second electrolyte correspond to Y-1 in Table 1 below, where Y corresponds to the number of Comparative Example 1 or Examples 2 to 17.
[0115] Step 207: performing a second high-temperature static process on the initial battery cell, wherein the temperature of the second high-temperature static process is 50° C. and the time is 36 hours.
[0116] The following tests were performed on the above Comparative Example 1 and Examples 2 to 17:
[0117] (1) Surface tension test: The first electrolyte and the second electrolyte corresponding to each embodiment were fully mixed in a mass ratio of 85:15 to obtain a mixed solution, and the surface tension of the mixed solution was measured by a surface tension meter at 25°C. Surface tension is a measure of the mutual attraction between molecules on the surface of a liquid, usually expressed in Newtons per meter (N / m). The smaller the surface tension, the better the wettability of the electrolyte, which is beneficial to improving the overall performance of the battery.
[0118] (2) Wetting time test: The first electrolyte and the second electrolyte corresponding to each embodiment were fully mixed in a mass ratio of 85:15 to obtain a mixed solution, and the mixed solution was dropped onto the surface of the negative electrode sheet to test the time it takes for the mixed solution to disappear. The shorter the wetting time, the better the wettability of the mixed solution.
[0119] (3) 25°C cycle capacity retention test: At 25°C, the lithium-ion battery corresponding to each embodiment is charged to the upper limit voltage at 1C constant current, then charged to the current of 0.05C at constant voltage, and then discharged to the lower limit voltage at 1C constant current. The charge and discharge test is performed for 1000 cycles, and the discharge capacity of the 500th cycle and the discharge capacity of the 1000th cycle are recorded. The capacity retention rate of the 500th cycle is calculated as (500th discharge capacity / first discharge capacity) × 100%; the capacity retention rate of the 1000th cycle is calculated as (1000th discharge capacity / first discharge capacity) × 100%.
[0120] (4) 45°C cycle capacity retention test: At 45°C, the lithium-ion battery corresponding to each embodiment is charged to the upper limit voltage at 1C constant current, then charged to the current of 0.05C at constant voltage, and then discharged to the lower limit voltage at 1C constant current. The charge and discharge test is performed for 1000 cycles, and the discharge capacity of the 500th cycle and the discharge capacity of the 1000th cycle are recorded. The capacity retention rate of the 500th cycle is calculated as (500th discharge capacity / first discharge capacity) × 100%; the capacity retention rate of the 1000th cycle is calculated as (1000th discharge capacity / first discharge capacity) × 100%.
[0121] (5) 45°C high temperature storage performance test: At 45°C, the lithium ion battery corresponding to each embodiment is charged to the upper limit voltage at 1C constant current, then charged to the current of 0.05C at constant voltage, and then discharged to the lower limit voltage at 1C constant current, and the discharge capacity of this time is recorded as the initial capacity C1. The battery is charged to the upper limit voltage at 1C constant current again, and then charged to the current of 0.05C at constant voltage. The fully charged battery is stored at 45°C for 15 days. After the expiration, it is placed at room temperature for at least 2 hours, and discharged to the lower limit voltage at 1C constant current. The discharge capacity C2 is recorded, and the capacity retention rate (%) is calculated as (C2 / C1)×100%. Then, it is charged to the upper limit voltage at 1C constant current and constant voltage at room temperature, and the current is cut off at 0.05C, and then discharged to the lower limit voltage at 1C constant current, and the recovery capacity C3 is recorded. The capacity recovery rate (%) is calculated as (C3 / C1)×100%.
[0122] (6) Energy efficiency test: At 25°C, the lithium-ion battery corresponding to each embodiment was charged to the upper limit voltage at a constant power of 0.5P, left to stand for 30 minutes, and then discharged to the lower limit voltage at a constant power of 0.5P, and left to stand for 30 minutes. Calculate the energy efficiency = discharge energy / charge energy.
[0123] Figure 4 The test results corresponding to Comparative Example 1 and Examples 2 to 17 provided in the embodiments of the present application.
[0124] In the surface tension test and the wetting time test, for Comparative Example 1 and Examples 2 to 17, the first electrolyte and the second electrolyte were precisely mixed in a mass ratio of 85:15 to obtain a mixed electrolyte, wherein the batteries corresponding to Comparative Example 1, Example 2 and Example 3 were the same as the mixed electrolyte in the final comprehensive electrolyte chemical composition. The experimental results show that, without considering the electrochemical reaction in the battery, the formulas of the same composition exhibit highly consistent physical properties, which are reflected in the two test results of surface tension and wetting time being basically consistent. This phenomenon is verified in the combinations of Comparative Example 1 / Example 2 / Example 3, Example 4 / Example 5 / Example 8 / Example 9, Example 6 / Example 7 / Example 10 / Example 15 and Example 11 / Example 12 / Example 13 / Example 14 / Example 16 / Example 17. By comparing Comparative Example 1 / Example 2 / Example 3 with other formula combinations, the introduction of additives and wetting stabilizers can improve the surface tension characteristics of the mixed electrolyte and shorten the wetting time, especially the effect of the wetting stabilizer is more significant, thereby effectively enhancing the overall wetting ability of the electrolyte.
[0125] Through the four key indicators of 25℃ cycle capacity retention test (normal temperature cycle test), 45℃ cycle capacity retention test (high temperature cycle test), 45℃ high temperature storage performance test (high temperature storage test) and energy efficiency test, the influence of electrolyte formula and injection method on battery performance was deeply discussed. The experimental results show that the secondary injection technology (Example 2 compared with Comparative Example 1) shows significant advantages in improving various performance indicators of the battery, especially in the later stage of the cycle, the improvement of capacity retention is more obvious. This phenomenon can be attributed to the directional repair effect of high concentration of vinylene carbonate in the second electrolyte on the formed SEI film.
[0126] Further comparison of the test data of Example 2 and Example 3 reveals that: when the vinylene carbonate content of the first electrolyte is higher than that of the second electrolyte in the secondary injection formula, since the main component of the SEI film depends on the additive in the first electrolyte, an excessively high content of vinylene carbonate may increase the interface impedance, thereby affecting the cycle performance and energy efficiency, but at the same time it can also enhance the capacity retention and recovery rate under high temperature storage conditions. This conclusion is further verified in the comparison of Example 6 and Example 7, indicating that the optimization of the content of vinylene carbonate in the first electrolyte requires a balance between cycle performance, energy efficiency and high temperature storage performance.
[0127] On the other hand, by comparing the performance of Example 4, Example 5, Example 6 with Example 2, the study found that adding 1,3-propane sultone, fluoroethylene carbonate, or a combination of the two to the first electrolyte can effectively improve the room temperature and high temperature cycle performance, among which 1,3-propane sultone is particularly significant for improving high temperature storage performance, but may slightly reduce energy efficiency. These results are consistent with the characteristics of 1,3-propane sultone enhancing the density and stability of the SEI film, and fluoroethylene carbonate improving low temperature performance and energy efficiency. On the whole, the combined use of fluoroethylene carbonate and 1,3-propane sultone (Example 6 scheme) can effectively combine the advantages of the two additives, showing a more excellent comprehensive effect in multiple performance indicators, and providing strong support for the overall improvement of battery performance.
[0128] By comparing the combinations of Example 4 / Example 8, Example 5 / Example 9 and Example 6 / Example 10, the influence of the distribution of additives in the first electrolyte and the second electrolyte was deeply explored. The experimental results once again verified the previous findings on the amount of vinylene carbonate: under the premise of a constant total additive amount, the nature and amount of the additives in the first electrolyte play a decisive role in the formation of the SEI film and the overall battery performance. Specifically, when 1,3-propane sultone was added to the first electrolyte (Example 4 compared to Example 8), the high temperature storage and high temperature cycle performance of the battery were significantly improved, but the room temperature cycle and energy efficiency were slightly reduced. In contrast, adding fluoroethylene carbonate to the first electrolyte (Example 5 compared to Example 9) improved the room temperature and high temperature cycle performance, but had a slight negative impact on high temperature storage and energy efficiency, which is consistent with the known interface repair and cycle enhancement properties of fluoroethylene carbonate. It is worth noting that when fluoroethylene carbonate and 1,3-propane sultone are added to the first electrolyte at the same time (Example 6 compared to Example 10), the battery performance shows a comprehensive optimization effect. Except for a slight decrease in energy efficiency, it shows significant improvements in cycle performance and storage stability.
[0129] By comparing the experimental results of Example 10, Example 11, Example 12, Example 13 and Example 14, the effect of adding the wetting stabilizer in different electrolytes was systematically evaluated. The data show that whether the wetting stabilizer is added to the first electrolyte or the second electrolyte, the normal temperature cycle and high temperature cycle performance of the battery can be significantly improved, and the high temperature storage performance has a certain positive effect. However, it is worth noting that the addition of the wetting stabilizer also leads to a slight decrease in energy efficiency. Unlike additives such as 1,3-propane sultone and fluoroethylene carbonate that directly participate in the formation of the SEI film, the main mechanism of action of the wetting stabilizer is to improve the wetting performance of the pole piece surface, rather than directly participating in the formation process of the SEI film. Therefore, the difference in the effect of adding the wetting stabilizer to the first electrolyte and the second electrolyte is relatively small. Nevertheless, the experimental results show that adding a wetting stabilizer (such as Example 11 and Example 12) to the second electrolyte can make it exist in more free forms, so that it can play a more effective role and obtain more ideal comprehensive performance.
[0130] When comparing Example 6 and Example 15, despite the use of the same electrolyte formula, various tests, including normal temperature and high temperature cycles, high temperature storage and energy efficiency, showed adverse effects when the injection volume was reduced. This is mainly due to the reduction in the amount of electrolyte, which leads to a series of problems such as drying up and lithium precipitation, thus having a negative impact on battery performance. However, when comparing Example 15 with Example 16 and Example 17, despite maintaining the same injection volume and adding a wetting stabilizer, its performance is comparable to that of the high injection volume state, which proves that the wetting stabilizer can still play a positive role under low injection volume conditions and achieve excellent long cycle performance.
[0131] In addition, in order to verify whether the rehydration treatment improves the consistency and quality of the battery, 30 batteries that were not rehydration treated were retained in the experiment, that is, the above step 205 was skipped, and the other steps were the same as the preparation of the above Example 2. Compared with Example 2, the 30 batteries that were not rehydration treated showed better consistency after rehydration treatment, and the capacity distribution and K value of the battery cells corresponding to Example 2 after manufacturing were more outstanding. Among them, the K value refers to the voltage drop of the battery per unit time, which is an indicator used to measure the self-discharge rate of lithium batteries.
[0132] Those skilled in the art will appreciate that the above-mentioned embodiments are specific examples for implementing the present application, and in practical applications, various changes may be made to the embodiments in form and detail without departing from the spirit and scope of the present application. Any person skilled in the art may make various changes and modifications without departing from the spirit and scope of the present application, and therefore the scope of protection of the present application shall be subject to the scope defined in the claims.
Claims
1. A method for preparing a lithium ion battery, characterized in that: include: Provide positive electrode sheets, negative electrode sheets and separators; The positive electrode sheet, the negative electrode sheet and the separator are wound or stacked and then placed into a housing to form an initial battery cell, wherein the separator is located between the positive electrode sheet and the negative electrode sheet; The initial battery cell is subjected to a first liquid injection process, wherein a first electrolyte is injected into the initial battery cell, wherein the first electrolyte comprises 0.5 wt% to 2 wt% of vinylene carbonate, 0.1 wt% to 2 wt% of 1,3-propane sultone, 0.1 wt% to 2 wt% of fluoroethylene carbonate, 5 wt% to 15 wt% of lithium salt and a non-aqueous organic solvent; and the injection amount of the first electrolyte is 3.5 g / Ah to 4 g / Ah; Performing a formation process on the initial battery cell; The initial battery cell is subjected to a second liquid injection process, wherein a second electrolyte is injected into the initial battery cell, wherein the second electrolyte comprises 5wt% to 20wt% of vinylene carbonate, 5wt% to 15wt% of lithium salt, 0.005wt% to 30wt% of a wetting stabilizer and the non-aqueous organic solvent; the wetting stabilizer is selected from one of 2-[ethyl[(heptadecafluorooctyl)sulfonyl]amino]ethanol polyoxyethylene ether, N-ethyl perfluorooctanesulfonamidoethyl methacrylate, fluorobenzene, 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether, hexafluoropropyl glycol and hexafluoropropylene oxide; the injection amount of the second electrolyte is 3.5g / Ah to 4g / Ah; After the initial battery cell is subjected to the formation process and before the initial battery cell is subjected to the second liquid injection process, the method further includes: performing a liquid replenishment treatment on the initial battery cell, in which the first electrolyte is replenished into the initial battery cell during the liquid replenishment treatment step; before the initial battery cell is subjected to the formation process, the method further includes: weighing the initial battery cell to obtain a first mass of the initial battery cell; after the initial battery cell is subjected to the formation process, the method further includes: weighing the initial battery cell to obtain a second mass of the initial battery cell; the mass of the first electrolyte replenished in the liquid replenishment treatment is the difference between the first mass and the second mass.
2. The method for preparing a lithium ion battery according to claim 1, characterized in that: The first electrolyte accounts for 65 wt % to 90 wt % of the total mass of the first electrolyte and the second electrolyte.
3. The method for preparing a lithium ion battery according to claim 1, characterized in that: The formation process includes: a first high-temperature static step, a negative pressure formation step and an aging static step.
4. The method for preparing a lithium ion battery according to claim 3, characterized in that: After the initial battery cell is subjected to the second liquid injection process, the method further includes: subjecting the initial battery cell to a second high-temperature static process, wherein the temperature of the second high-temperature static process is greater than the temperature of the first high-temperature static process.
Citation Information
Patent Citations
Lithium ion battery electrolyte, preparation method thereof, and lithium ion battery
CN105322227A
Lithium ion battery assembly method and lithium ion battery
CN110854439A
Method for improving formation interface of lithium ion battery
CN113097667A
Method and device for avoiding residual crystallization of electrolyte
CN115832442A
Cited By
Pole piece structure, roll core and lithium ion battery
CN224164357U